Prospective associations between total, animal, and vegetable calcium intake and metabolic syndrome in adults aged 40 years and older. Issue 7 (July 2020) - Woo, Hye Won; Lim, Young-Hyo; Kim, Mi Kyung; Shin, Jinho; Lee, Young-Hoon; Shin, Dong Hoon; Shin, Min-Ho; Choi, Bo Youl
Summary: Background & aims: Calcium (Ca) consumption may contribute to a decreased risk of developing metabolic syndrome (MetS). However, epidemiologic evidence on the association between Ca intake and MetS is limited. This study aimed to evaluate the association between dietary Ca intake (animal-based Ca and vegetable-based Ca separately, as well as total Ca intake) and the incidence risk of MetS and its components in the Korean Multi-Rural Communities Cohort (MRCohort). Methods: A total of 5509 participants who did not have MetS were enrolled. Dietary Ca intake was calculated using a food frequency questionnaire composed of 106 items. Results: After 18, 880 person-years of follow-up, 876 participants had developed de novo MetS. A significant inverse association between dietary total Ca intake and MetS were observed (incidence rate ratio (IRR) = 0.62, 95% confidence interval (CI) = 0.48–0.81, P for trend = 0.002 for the highest quartile of total Ca intake compared with the lowest quartile). Trends for animal Ca (IRR = 0.77, 95% CI = 0.62–0.97, P for trend = 0.039) and vegetable Ca (IRR = 0.54, 95% CI = 0.40–0.73, P for trend <0.001) were similar. The individual components of overall MetS were also inversely related to total, animal, and vegetable Ca. The tendency for an inverse association was more evident in the group with two of any of the metabolic abnormalities of MetS at baseline than in the group with no more than one MetS component. Conclusions: Our findings indicate that a relatively high dietary intake of Ca is associated with lower risk of MetS.